The IMPLEMENTASI MODEL HIPNOTERAPI UNTUK MENGURANGI GEJALA RELAPSE KORBAN PENYALAHGUNAAN NARKOBA - Supiadi, Epi (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2024)
Against the background of optimism that hypnotherapy techniques have great potential to increase the effectiveness of treating victims of drug abuse in the future, the implementation of this hypnotherapy model specifically aims to reduce the symptoms of relapse in victims of drug abuse. Implementation of the model begins with the application of The AWARE questionnaire from Gorski to determine various symptoms of relapse, then continues with step (1) pre-induction which includes building relationships with prospective clients, hypnotherapy training and suggestibility tests, and building contracts; (2) Induction which includes eyelid fixation; flying hand; total body relaxation; progressive relaxation; and rapid induction; (3) Deepening using calculation and imagination, as well as a depth level test using ideo motor response; (4) Suggestion therapy/therapeutic intervention in the form of a narrative created specifically to produce a healing effect, especially the symptoms of relapse found; (5) Termination as a technical step to return the Subject to normal conditions. The implementation of the hypnotherapy model using experimental methods has been proven to be able to reduce relapse symptoms in drug abuse victims. Keywords: Hypnotherapy model, Relapse Symptoms, Drug Abuse Victims.